Study on the Effect of Citric Acid and Sodium Chloride on Shredded Tuna (Thunus albacares) Meat (Abon lima) - Hari Purnomo; Sutarjo Surjoseputro; Toni Mali (Indonesian Association of Food Technologists, 2003)
Tuna (Thunus albacares) is usually processed as canned products and in other forms such as shredded (abon) tuna which is produced in home industries. 'Fishy' flavour of shredded tuna is the main problem, due to the trimethylamine (TMA) formation. Citric acid and sodium chloride can minimize this fishy' flavor, and avoid deterioration by decreasing the water activity. The best treatment was combination between 0.5% citric acid and 1.5% sodium chloride.